Synthesis and bioactivity of analogues of the marine antibiotic tropodithietic acid - Rabe, Patrick; Klapschinski, Tim A.; Brock, Nelson L.; Citron, Christian A.; D’Alvise, Paul; Gram, Lone; Dickschat, Jeroen S. (Beilstein Journal of Organic Chemistry, 2014)
Tropodithietic acid (TDA) is a structurally unique sulfur-containing antibiotic from the Roseobacter clade bacterium Phaeobacter inhibens DSM 17395 and a few other related species. We have synthesised several structural analogues of TDA and used them in bioactivity tests against Staphylococcus aureus and Vibrio anguillarum for a structure–activity relationship (SAR) study, revealing that the sulfur-free analogue of TDA, tropone-2-carboxylic acid, has an antibiotic activity that is even stronger than the bioactivity of the natural product. The synthesis of this compound and of several analogues is presented and the bioactivity of the synthetic compounds is discussed.
Keywords: antibiotics; natural products; Roseobacter; SAR study; tropodithietic acid; tropone

(untitled) - Liang, L. (University of Göttingen, 2003)

(untitled) - Cane, D. E.; Wu, Z.; Van Epp, J. E. (J. Am. Chem. Soc., 1992)

(untitled) - Greer, E. M.; Aebisher, D.; Greer, A.; Bentley, R. (J. Org. Chem., 2008)

(untitled) - Berger, M.; Brock, N. L.; Liesegang, H.; Dogs, M.; Preuth, I.; Simon, M.; Dickschat, J. S.; Brinkhoff, T. (Appl. Environ. Microbiol., 2012)

(untitled) - Teufel, R.; Gantert, C.; Voss, M.; Eisenreich, W.; Haehnel, W.; Fuchs, G. (J. Biol. Chem., 2011)

(untitled) - Geng, H.; Bruhn, J. B.; Nielsen, K. F.; Gram, L.; Belas, L. (Appl. Environ. Microbiol., 2008)

(untitled) - Thole, S.; Kalhoefer, D.; Voget, S.; Berger, M.; Engelhardt, T.; Liesegang, H.; Wollherr, A.; Kjelleberg, S.; Daniel, R.; Simon, M.; Thomas, T.; Brinkhoff, T. (ISME J., 2012)

(untitled) - Brock, N. L.; Nikolay, A.; Dickschat, J. S. (Chem. Commun., 2014)

(untitled) - Thiel, V.; Brinkhoff, T.; Dickschat, J. S.; Wickel, S.; Grunenberg, J.; Wagner-Döbler, I.; Simon, M.; Schulz, S. (Org. Biomol. Chem., 2010)

(untitled) - Seyedsayamdost, M. R.; Case, R. J.; Kolter, R.; Clardy, J. (Nat. Chem., 2011)

(untitled) - Brinkhoff, T.; Bach, G.; Heidorn, T.; Liang, L.; Schlingloff, A.; Simon, M. (Appl. Environ. Microbiol., 2004)

(untitled) - Neu, A. K.; Månsson, M.; Gram, L.; Prol-García, M. J. (Appl. Environ. Microbiol., 2014)

(untitled) - Porsby, C. H.; Webber, M. A.; Nielsen, K. F.; Piddock, L. J. V.; Gram, L. (Antimicrob. Agents Chemother., 2011)

(untitled) - Do, Y.-S.; Sun, R.; Kim, H. J.; Yeo, J. E.; Bae, S.-H.; Koo, S. (J. Org. Chem., 2009)

(untitled) - Seitz, G.; van Gemmern, R. (Synthesis, 1987)

(untitled) - Schultz, A. G.; Holoboski, M. A. (Tetrahedron Lett., 1993)

(untitled) - Citron, C. A.; Rabe, P.; Dickschat, J. S. (J. Nat. Prod., 2012)

(untitled) - Ruiz-Ponte, C.; Cilia, V.; Lambert, C.; Nicolas, J. L. (Int. J. Syst. Bacteriol., 1998)

(untitled) - Martens, T.; Heidorn, T.; Pukall, R.; Simon, M.; Tindall, B. J.; Brinkhoff, T. (Int. J. Syst. Evol. Microbiol., 2006)

(untitled) - Buddruhs, N.; Pradella, S.; Göker, M.; Päuker, O.; Pukall, R.; Spröer, C.; Schumann, P.; Petersen, J.; Brinkhoff, T. (Int. J. Syst. Evol. Microbiol., 2013)

Guideline M7-A7: Methods for dilution antimicrobial susceptibility tests for bacteria that grow aerobically; Approved Standard–Seventh Edition - Wikler, M. A.; Cockerill, F. A.; Craig, W. A.; Dudley, M. N.; Eliopoulos, G. M.; Hecht, D. W.; Hindler, J. F.; Ferraro, M. J.; Swenson, J. M.; Low, D. E.; Sheehan, D. J.; Tenover, F. C.; et al. (Clinical Laboratory Standards Institute, 2006)

(untitled) - Novick, R. (Virology, 1967)

(untitled) - Skov, M. N.; Pedersen, K.; Larsen, J. L. (Appl. Environ. Microbiol., 1995)